2020
DOI: 10.1017/s1041610220000289
|View full text |Cite
|
Sign up to set email alerts
|

Is preparation for end of life associated with pre-death grief in caregivers of people with dementia?

Abstract: ABSTRACTObjectives:Family caregivers of people with dementia can experience loss and grief before death. We hypothesized that modifiable factors indicating preparation for end of life are associated with lower pre-death grief in caregivers.Design:Cross-sectional. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…The three-tiered public health approach to bereavement suggests that most people will manage grief with support through their social network (Aoun et al, 2015). Our recent work has shown that among a range of factors relating to preparation for end of life, social support had the greatest impact on grief while caring for a relative with dementia (Moore et al, 2020). However, as we are confined to our homes, access to our social network may be reduced.…”
Section: Grief and Bereavementmentioning
confidence: 99%
“…The three-tiered public health approach to bereavement suggests that most people will manage grief with support through their social network (Aoun et al, 2015). Our recent work has shown that among a range of factors relating to preparation for end of life, social support had the greatest impact on grief while caring for a relative with dementia (Moore et al, 2020). However, as we are confined to our homes, access to our social network may be reduced.…”
Section: Grief and Bereavementmentioning
confidence: 99%
“…Much research has focused on exploring relationships after death when negative outcomes have already occurred (e.g., complicated grief, depression, anxiety) (Nielsen et al, 2016;Schulz et al, 2015). However, little is known about the relationship between preparedness and pre-death grief (Moore et al, 2020).…”
mentioning
confidence: 99%
“…In the paper by Moore et al (2020), the authors explored the relationship between pre-death grief and death preparedness among family caregivers of persons with dementia. Moore et al (2020) hypothesized that higher levels of pre-death grief were associated with lower levels of death preparedness.…”
mentioning
confidence: 99%
See 2 more Smart Citations